Biogenesis of the eukaryotic proteasome - Hochstrasser, Mark (Henry Stewart Talks, 2012)
The ubiquitin-proteasome system, Proteasome composition and structure, 20S proteasome core particle assembly, 19S regulatory particle assembly, Update talk: The ‘resolution revolution’, Update talk: Proteasome regulatory particle assembly factor structure and function, Update talk: Assembly factor inhibitors, Update talk: Location of proteasome assembly in the cell
Updated at 2022/03/30